Correlation Between Leadership Competencies of Islamic Religious Education Teachers and Students' Religiosity at SMK Muhammadiyah Prambanan Yogyakarta (Program Studi Pendidikan Agama Islam, 2021)
Islamic Religious Education teachers as professional educators must be able to develop student religiosity in schools. This study aims to determine the correlation between PAI teacher leadership competence and student religiosity at SMK Muhammadiyah Prambanan Yogyakarta. This research is a quantitative research. The research subjects were 125 students of SMK Muhammadiyah Prambanan Yogyakarta, which were selected using proportional random sampling technique. Data was collected using psychological scale methods, interviews, and documentation. The data collection instrument test used the Validity and Reliability test, the analysis prerequisite test used the Linearity test and the Normality test. Data analysis used descriptive statistical analysis and product Moment correlation with SPSS program. The results showed: 1) the religiosity of SMK Muhammadiyah Prambanan Yogyakarta students was in the medium category. 2) The leadership competence of PAI teachers at SMK Muhammadiyah Prambanan Yogyakarta is in the medium category. 3) There is a very significant positive relationship between the leadership competence of PAI teachers and the religious behavior of students at SMK Muhammadiyah Prambanan Yogyakarta, with rxy = 0.598 and p of 0.000